Computational modeling of intravitreal ranibizumab kinetics: Predicting macular drug concentration and half-life - Jabia Mostofa Chowdhury (PLoS ONE, 2026)
Ranibizumab is a key anti-VEGF therapeutic used to improve treatment efficacy and reduce injection frequency in neovascular retinal diseases. Because experimental pharmacokinetic data in humans are limited, computational modeling provides an effective means to predict ocular drug behavior. In this study, a three-dimensional computational model of the human eye was developed in COMSOL Multiphysics 6.3 to analyze the pharmacokinetics of ranibizumab following intravitreal injection. The model also quantified drug concentration near the macula, the primary target site for neovascular disease, and evaluated it against the minimum threshold concentration required for VEGF suppression. Fluid flow in the vitreous was represented by Darcy’s law, while drug convection and diffusion were modeled using the transport of diluted species equation. Four physiological scenarios combining vitreous state (normal vs. partially liquefied) and elimination pathways (anterior dominant vs. both routes) were simulated. Predicted intravitreal half-lives ranged from 2.7 to 4.4 days, consistent with reported human data (2.4 ~ 9 days). The model demonstrates a plausible representation of physiologically relevant ocular pharmacokinetics and provides a computational framework that may assist in exploring dosing strategies and informing the design of intravitreal drug delivery systems.